Pengaruh Beban Kerja dan Resiliensi terhadap Job Burnout dengan Stres Kerja sebagai Variabel Mediasi - Busti, Muharramainil Fajri; Yulihasri; Rivai, Harif Amali (Jurnal Informatika Ekonomi Bisnis, 2023)
This study aims to determine the effect of workload, resilience, work stress on job burnout. This research was conducted at Aisyiyah Hospital Padang. The population in this study are all nurses who work in hospitals. Aisyiyah Padang as many as 48 people. Meanwhile, the sampling method used in this study used a saturated sampling method where the entire population in this study became a research sample totaling 48 people. The data analysis technique in this study was carried out by means of regression analysis using PLS structural model analysis assisted by using Smart PLS 4.0 software. The results showed that workload had a positive and significant effect on work stress; resilience has a negative and significant effect on work stress; workload has a positive and significant effect on job burnout; resilience has a negative and significant effect on job burnout; work stress has a positive and significant effect on job burnout; workload has a positive and significant effect on job burnout which is mediated by work stress; and resilience has a negative and significant effect on job burnout which is mediated by work stress.